serafina67 *urgently requires life* - Day, Susie (Susanna Mary), 1975- (New York : Scholastic Press, 2008)
Fifteen-year-old Sarah tracks on a blog her efforts to meet her "New Blog Resolutions," especially to be happy again by the anniversary of "The Incident," despite her father's impending remarriage to the Monster, her mother's unhappiness, and huge fluctuations in her own popularity.
G10
Keywords: Blogs -- Fiction; Interpersonal relations -- Fiction; Happiness -- Fiction; Family problems -- Fiction; Remarriage -- Fiction; High schools -- Fiction; Schools -- Fiction; England -- Fiction